Vasculo-Neuronal Coupling and Neurovascular Coupling at the Neurovascular Unit: Impact of Hypertension - Presa, Jessica L.; Saravia, Flavia; Bagi, Zsolt; Filosa, Jessica A. (Frontiers in Physiology, 2020)
Components of the neurovascular unit (NVU) establish dynamic crosstalk that regulates cerebral blood flow and maintain brain homeostasis. Here, we describe evidence for cells of the NVU contributing to critical physiological processes such as cerebral autoregulation, neurovascular coupling, and vasculo-neuronal coupling. We discuss how alterations in the cellular mechanisms governing NVU homeostasis can lead to pathology for which vascular cell and astrocyte function may play a key role. Because hypertension is a modifiable risk factor for stroke and accelerated cognitive decline in aging, we focus on hypertension-associated changes on cerebral arteriole function and structure, and how these may contribute to cognitive decline. We gather evidence concerning cognitive loss in hypertension and the link with dementias like Alzheimer’s disease. Collectively, we summarize how vascular dysfunction, hypoperfusion, oxidative stress and inflammatory processes can uncouple communication at the NVU impairing cerebral perfusion and contributing to neurodegeneration.